New mathematical model for Islamic unit trust - Puspa Liza, Ghazali; Md Habibur, Rahman; Nik Hazimi, Mohammed Foziah (2019)
The demand for Islamic unit trust which is the alternative to the interest- based market become increasing day by day. This encourages the Malaysian government to take the various intervention and measures, so that interest free market which is Shariah Compliant can be introduced. The aim of this research is to construct a new formulation of Islamic unit trust for better incomes of Muslim customers’. The method of this researches to derivate a new model by using the new concept of dividend. In findings, the new model of formulation can be contrasted in Islamic unit trust. This new model is a suggestion for unit trust management to be applied in the future time.